Geriatrics as a specialty: Insights from Mexican medical students’ decision-making process - Carolina Gómez-Moreno; Tania Vives-Varela; Alfonso Gulias-Herrero; José Alberto Ávila-Funes; Ayari Pérez-Méndez; Melchor Sánchez-Mendiola; Carlos Gutiérrez-Cirlos (PLoS ONE, 2025)
Main objective To identify the elements associated with the decision to select or reject geriatrics as a medical specialty in Mexico. Methods Qualitative, with the focus group technique to obtain data. Two groups included students who rejected geriatrics, regardless of the specialty they chose, and two groups included students who chose geriatrics, interviews via Zoom were conducted. Data was analyzed qualitatively based on grounded theory. Results Thirty-four students were included in the final sample (52% women), mainly from the Central region of the country (44%). Students were mainly in their last year of medical school (97%). Previous experiences with older patients and older close relatives, both positive and negative, were important in choosing the specialty of geriatrics for most students. In contrast, personality, and interpretation of the experiences as good or bad was the main differentiator between groups. For those who did not choose geriatrics, the main factor was the lack of knowledge regarding contents, aims, and professional opportunities for geriatricians. Previous experiences with geriatric care influenced positively towards choosing geriatrics as a medical specialty. High-quality, structured exposure to geriatrics should be encouraged among medical students in order to increase knowledge and eventually interest in the specialty.